Potential Effects of Elimination of the Black Race Coefficient in eGFR Calculations in the CREDENCE Trial. Issue 3 (March 2022) - Charytan, David M.; Yu, Jie; Jardine, Meg J.; Cannon, Christopher P.; Agarwal, Rajiv; Bakris, George; Greene, Tom; Levin, Adeera; Pollock, Carol; Powe, Neil R.; Arnott, Clare; Mahaffey, Kenneth W.
Visual Abstract: Abstract : Background and objectives: The effect of including race in the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation on screening, recruitment, and outcomes of clinical trials is unclear. Design, setting, participants, & measurements: The inclusion and outcomes of participants in the Canagliflozin and Renal Events in Diabetes with Established Nephropathy Clinical Evaluation (CREDENCE) trial, which randomized individuals with type 2 diabetes and CKD to canagliflozin or placebo, were evaluated after calculating eGFR using the 2009 CKD-EPI creatinine equation with and without a race-specific coefficient or the 2021 CKD-EPI creatinine equation. Treatment effects were estimated using proportional hazards models and piecewise linear mixed effects models for eGFR slope. Results: Of 4401 randomized participants, 2931 (67%) were White participants, 224 (5%) were Black participants, 877 (20%) were Asian participants, and 369 (8%) participants were other race. Among randomized participants, recalculation of screening eGFR using the 2009 equation without a race-specific coefficient had no effect on the likelihood of non-Black participants meeting inclusion criteria but would have excluded 22 (10%) randomized Black participants for eGFR<30 ml/min per 1.73 m 2 . Recalculation with the 2021 equation would have excluded eight (4%) Black participants for low eGFR and one (0.4%) Black participant for eGFR≥90 ml/min per 1.73 m 2, whereas 30 (0.7%) and 300 (7%) non-Black participants would have been excluded for low and high eGFR, respectively. A high proportion (eight of 22; 36%) of end points in Black participants occurred in individuals who would have been excluded following recalculation using the race-free 2009 equation but not when recalculated with the 2021 equation (one of eight; 13%). Cardiovascular and kidney treatment effects remained consistent across eGFR categories following recalculation with either equation. Changes in estimated treatment effects on eGFR slope were modest but were qualitatively larger following recalculation using the 2021 equation. However, the effect of canagliflozin on chronic change in eGFR was attenuated by 7% among Black participants and increased 6% in non-Black participants. Conclusions: In the CREDENCE trial, eGFR recalculation without the race-specific coefficient had small but potentially important effects on event rates and the relative proportion of Black participants without substantially changing efficacy estimates. Clinical Trial registry name and registration number: Canagliflozin and Renal Events in Diabetes with Established Nephropathy Clinical Evaluation (CREDENCE), NCT02065791